Microeconomics - Besanko, David, 1955-; Braeutigam, Ronald R. (Ronald Ray); Gibbs, Michael, 1962- (Hoboken, NJ : John Wiley, 2011)
"Business professionals that struggle to understand key concepts in economics and how they are applied in the field rely on Microeconomics. The fourth edition makes the material accessible while helping them build their problem-solving skills. It includes numerous new practice problems and exercises that arm them with a deeper understanding. Learning by Doing exercises explore the theories while boosting overall math skills. Graphs are included throughout the mathematical discussions to reinforce the material. In addition, the balanced approach of rigorous economics gives business professionals a more practical resource."--
Machine generated contents note: Part 1: Introduction To Microeconomics -- Chapter 1: Analyzing Economic Problems -- Chapter 2: Demand and Supply Analysis -- Part 2: Consumer Theory -- Chapter 3: Consumer Preferences and the Concept of Utility -- Chapter 4: Consumer Choice -- Chapter 5: The Theory of Demand -- Part 3: Production and Cost Theory -- Chapter 6: Inputs and Production Functions -- Chapter 7: Costs and Cost Minimization -- Chapter 8: Cost Curves -- Part 4: Perfect Competition -- Chapter 9: Perfectly Competitive Markets -- Chapter 10: Competitive Markets: Applications -- Part 5: Market Power -- Chapter 11: Monopoly and Monopsony -- Chapter 12: Capturing Surplus -- Part 6: Imperfect Competition and Strategic Behavior -- Chapter 13: Market Structure and Competition -- Chapter 14: Game Theory and Strategic Behavior -- Part 7: Special Topics -- Chapter 15: Risk and Information -- Chapter 16: General Equilibrium -- Chapter 17: Externalities and Public Goods.
Includes index.
Keywords: Microeconomics